MENGUKUR KINERJA KEUANGAN KOPERASI SIMPAN PINJAM (KSP) CU BANGUN SEJAHTERA BANGUNTAPAN KABUPATEN BANTUL - Mujino, Mujino; Udayana, Ibn (Jurnal Nusantara Aplikasi Manajemen Bisnis, 2018)
This research drive to study and analysing about financial performent on Bangun Sejahtera cooperative enterprise in Banguntapan, Bantul, stressing of Efficiency and productivity. Effisiency and productivity are very importance to survival enterprise, and it tools valuetion manajemen performent. Productivity and efficiency are the key success in business action now and to the future. Productivity shown from two viewpoints as, psychological and technical viewpoint. From psichologicaly, productivity is a mentality behavior, that present must be best than yesterday, and the future must be best than to day. Manager must be has character, value system and personal believe system. Base on technical method, productivity beable formula as: output / input, and to measure, how many output unit will be get from unit input expenditure. Increasing Productivity shown that its best management kinerja and if decreasing productivity, show that is bad management kinerja. In this research, productivity proxy as : Operational productivity, profit margin and owners equity rate of return. Effisiency is a tools to measure unit input expenditure,to get output unit. The following efficiency formula as: input : output Research result a long in seven years shown that productivity on Bangun Sejahtera cooperaitive enterprise go to decreasing, but no significant. Operiting productivity from elevent year (2011) to 2017 shown as : 1,72 , 1,49 , 1,57 , 1,45 , 1,29 , 1,30 , 1,26, avarage 1,44. Profit margin from elevent year to 2017 show as: 41,71 , 32,74 , 36,45 , 31,16 , 22,23 , 23,12 , 20,58 avarage 29,71. Effisientcy a long a sevent year shown as: 2011 = 0,58, 2012 = 0,67, 2013 = 0,64, 2014 = 0,69, 2015 = 0,78, 2016 = 0,77 , 2017 = 0,79. Avarage= 0,73.